The use of patient-reported outcome tools in Gynecologic Oncology research, clinical practice, and value-based care - Moss, Haley A.; Havrilesky, Laura J. (Gynecologic oncology, 2018)
Patient-reported outcomes (PRO) are defined as a report of a patient's symptoms, function and general well-being that comes directly from the patient, without interpretation of the response by a medical provider. As greater emphasis is placed on high-quality, patient-centered care, the importance of PROs has become widely accepted by policymakers, third party payers, medical societies, health care systems and clinical researchers. Despite increased recognition of the importance of PROs, they have not become a widely-implemented part of clinical care and their use in clinical research has been limited by methodological concerns. Health service researchers and providers are working to standardize and develop new methods to improve implementation of PROs in clinical and research settings. This article reviews the development of PRO measurement tools, implementation in the healthcare setting and relevance in clinical trials, with a focus on clinical care and research in gynecologic oncology. •Patient reported outcomes (PROs) are now used in both research and clinical care.•PROs play an important role in supporting progression-free survival endpoints in clinical trials.•Integration of PROS into electronic medical records is a component of alternative payment models.